Multivariate logistic regression analysis to explore the high-risk factors of deep vein embolism/pulmonary embolism after knee replacement in the elderly - Ming Liu; Zhanwen Zhou; Xiaohu Ma; Jinguo Ma; Xiaojin Wu; Binghan Chen; Yanbin Tian (Journal of Orthopaedic Surgery)
Objective This study aims to identify and quantify the high-risk factors for deep vein thrombosis (DVT) and pulmonary embolism (PE) in elderly patients undergoing total knee replacement (TKA). Methods 621 patients who underwent TKA were divided into DVT/PE positive group ( N = 52) and a negative group ( N = 569). Result Statistically significant differences were observed in the following factors: Caprini score (χ 2 = 11.385, p < .001), prevalence of chronic obstructive pulmonary disease (COPD) (χ 2 = 4.502, p = .034), history of heart failure (χ 2 = 4.326, p = .012), duration of surgery (t = 3.723, p = .002), and early postoperative activity (χ 2 = 4.014, p = .045). The incidence of DVT/PE was significantly higher in the very high-risk group compared to the high-risk group (9.89% vs 4.84%, χ 2 = 2.080, p = .032). Multivariate logistic regression analysis identified the Caprini score as an extremely high-risk factor (adjusted OR = 2.87, 95% CI: 1.53-5.39, p = .001), alongside COPD (OR = 1.94, 95% CI: 1.08-3.48, p = .026), history of heart failure (OR = 1.68, 95% CI: 1.01-2.78, p = .048), and surgical duration exceeding 2 hours (OR = 1.35, 95% CI: 1.08-1.68, p = .008) as independent risk factors. The model, developed using multi-factor regression variables, demonstrates strong predictive performance for the occurrence of DVT/PE, with an area under the receiver operating characteristic curve of 0.842 (95%CI: 0.791-0.894). Conclusion In elderly patients undergoing TKA, even with standard anticoagulation prophylaxis, a high Caprini risk score, COPD, a history of heart failure, and prolonged operative time remain independent risk factors for DVT. Early postoperative mobilization has been shown to have a protective effect.